Poly I:C-priming of adipose-derived mesenchymal stromal cells promotes a pro-tumorigenic phenotype in an immunocompetent mouse model of prostate cancer - Rivera-Cruz, Cosette M.; Kumar, Shreya; Figueiredo, Marxa L. (Frontiers in Cell and Developmental Biology, 2023)
While BM-MSC remain the most commonly studied MSC subtype and were the focus of original MSC polarization paradigm reports, MSC derived from other tissues may provide advantages for clinical use such as higher relative abundance and differential functional potential. In our previous work, we had identified phenotypical and functional consequences of TLR3 or TLR4 priming on ASC that partially resembled those previously reported for BM-MSC. In our assessment, LPSpriming of ASC rendered them immunostimulatory in immune killing assay coculture assays in the presence of human prostate adenocarcinoma cells and stimulated peripheral blood mononuclear cells. Understanding that tumorigenesis is a complex process involving many other tumor microenvironment components and other supportive tissues, we aimed to evaluate the consequences of TLR-priming in an immunocompetent model of androgen independent prostate cancer by assessing changes in tumor progression, gene expression and immune composition of tumors treated with TLR-primed ASC. This work expands on the impact of primed ASC on the prostate tumor microenvironment.